2015
DOI: 10.1007/s00424-015-1717-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of the isolated, perfused normoxic heart to pyruvate dehydrogenase activation by dichloroacetate and pyruvate

Abstract: Dichloroacetate (DCA) and pyruvate activate pyruvate dehydrogenase (PDH), a key enzyme that modulates glucose oxidation and mitochondrial NADH production. Both compounds improve recovery after ischemia in isolated hearts. However, the action of DCA and pyruvate in normoxic myocardium is incompletely understood. We measured the effect of DCA and pyruvate on contraction, mitochondrial redox state, and intracellular calcium cycling in isolated rat hearts during normoxic perfusion. Normalized epicardial NADH fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 52 publications
4
32
0
1
Order By: Relevance
“…The levels of most of the examined genes were increased after 48 h of treatment and some were upregulated only following 72 h of treatment. Interestingly, Bmal1 level was downregulated after treatment with rOly, consistent with the data presented by Nam et al (33) who demonstrated inhibition of this gene during brown adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The levels of most of the examined genes were increased after 48 h of treatment and some were upregulated only following 72 h of treatment. Interestingly, Bmal1 level was downregulated after treatment with rOly, consistent with the data presented by Nam et al (33) who demonstrated inhibition of this gene during brown adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The pyruvate dehydrogenase complex converts pyruvate into acetyl-CoA, which may then be used in the citric acid cycle for cellular respiration [77]. The reaction catalyzed by pyruvate dehydrogenase (E1) is considered to be the rate-limiting reaction in the pyruvate dehydrogenase complex [77, 78]. The present results showed that (-)-HCA treatment significantly increased PDH (E1) protein content in primary chicken hepatocytes.…”
Section: Discussionsupporting
confidence: 53%
“…Animals were anesthetized with 3-5% isoflurane, the heart was excised and then transferred to a temperature-controlled (37°C) constant-pressure (70 mmHg) Langendorff perfusion system. Excised hearts were perfused with Krebs-Henseleit buffer throughout the duration of the experiment, as previously described (<1 hour)(12,49,50). Three electrodes were positioned to acquire a far-field electrocardiogram in the lead II configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent dyes were added sequentially, as a bolus, through a bubble trap located proximal to the aortic cannula. Based on predetermined myocardial staining time for each dye, 50 μg Rhod-2AM(1,49) was added first and allowed to stabilize for 10 min, followed by 62.1 μg RH-237 staining for 1 min(12). The myocardial tissue was re-stained by RH237 if needed throughout the duration of the experiment(53).…”
Section: Methodsmentioning
confidence: 99%